2012
DOI: 10.1186/cc11189
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety in pre-hospital emergency tracheal intubation: a comprehensive meta-analysis of the intubation success rates of EMS providers

Abstract: IntroductionPre-hospital airway management is a controversial subject, but there is general agreement that a small number of seriously ill or injured patients require urgent emergency tracheal intubation (ETI) and ventilation. Many European emergency medical services (EMS) systems provide physicians to care for these patients while other systems rely on paramedics (or, rarely, nurses). The ETI success rate is an important measure of provider and EMS system success and a marker of patient safety.MethodsWe condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
116
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 69 publications
15
116
3
4
Order By: Relevance
“…Based on these findings, it may be difficult to acquire and maintain intubation skills with the MCL. Some previous studies have reported analogous conclusions to these [24][25][26][27].…”
Section: Discussionsupporting
confidence: 68%
“…Based on these findings, it may be difficult to acquire and maintain intubation skills with the MCL. Some previous studies have reported analogous conclusions to these [24][25][26][27].…”
Section: Discussionsupporting
confidence: 68%
“…[144][145][146][147][148][149][150] Further, prehospital intubation is not always available and the ability to perform this procedure safely varies among prehospital EMS personnel, with physicians having the highest success rates. [144][145][146][147][148][149][150][151] Prioritizing advanced airway management and spinal immobilization may also delay release and rescue procedures as well as make the trauma examination more difficult, both at the scene, during transport, and at admittance. 13,96,152 Delayed definitive care can be detrimental for patients with non-neurological critical injuries, and importantly, also lead to neurological progression, because spinal injuries are often neurologically unstable, but biomechanically stable in the acute phase.…”
mentioning
confidence: 99%
“…Therefore, advanced airway management is essential. Success rates in prehospital airway management vary, and a meta-analysis of prehospital care providers comparing paramedic and physician ETI revealed significant differences in success rates in favour of physicianstaffed services [9,10]. The ETI success rate of physicians in our group was 98.4%.…”
Section: Discussionmentioning
confidence: 93%